Development and validation of a SNP‐based assay for inferring the genetic ancestry of rhesus macaques (Macaca mulatta). Issue 11 (20th June 2014) - Kanthaswamy, Sree; Johnson, Zachary; Trask, Jessica Satkoski; Smith, David G.; Ramakrishnan, Ranjani; Bahk, Jason; Ng, Jillian; Wiseman, Roger; Kubisch, H. Michael; Vallender, Eric J.; Rogers, Jeffrey; Ferguson, Betsy
<x xml:space="preserve">Abstract</x> Rhesus macaques (Macaca mulatta) are an important primate model species in several areas of biomedical research. The wide geographic distribution of this species has led to significant genetic differentiation among local and regional populations. These regional differences can be important factors in the selection of the most appropriate subjects for particular research studies, as animals from different populations can respond differently to the same experimental treatment. Consequently, it is valuable to confirm the ancestry of individual rhesus monkeys from geographically distinct populations. Using DNA samples obtained from rhesus macaques from six National Primate Research Centers, we tested a set of 384 potential ancestry informative single nucleotide polymorphisms (SNPs) and identified a final panel of 91 SNPs that can reliably distinguish Indian‐origin from Chinese‐origin rhesus monkeys. This genetic test can be used to determine the ancestral origin of animals and to detect individuals that are hybrids between these two regional populations. To demonstrate use of the SNP panel, we investigated the ancestry of 480 animals from the Yerkes NPRC (YNPRC) for which the colony records were insufficient to clearly establish ancestry. Three of the YNPRC animals tested were determined to be hybrids. This SNP ancestry tool will be useful to researchers, colony managers, and others who wish to evaluate the ancestral origin of individual rhesus macaques, and therefore will facilitate more effective and efficient use of these animals in biomedical research. Am. J. Primatol. 76:1105–1113, 2014. © 2014 Wiley Periodicals, Inc.